Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Recombinant production, characterization and industrial application testing of a novel acidic exo/endo-chitinase from Rasamsonia emersonii - Kelly Dwyer; Ian S. Bentley; David A. Fitzpatrick; Aliabbas A. Saleh; Emma Tighe; Eibhilin McGleenan; Darragh Gaffney; Gary Walsh (Extremophiles, 2023)

Geographical variation in genetic structure of an Atlantic Coastal Forest frog reveals regional differences in habitat stability - SARAH W. FITZPATRICK; CINTHIA A. BRASILEIRO; CÉLIO F. B. HADDAD; KELLY R. ZAMUDIO (Molecular Ecology, 2009)
Climatic oscillations throughout the Pleistocene combined with geological and topographic complexity resulted in extreme habitat heterogeneity along the Atlantic coast of Brazil. Inferring how these historic landscape patterns have structured the current diversity of the region's biota is important both for our understanding of the factors promoting diversification, as well as the conservation of this biodiversity hotspot. Here we evaluate potential historical scenarios of diversification in the Atlantic Coastal Forest of Brazil by investigating the population genetic structure of a frog endemic to the region. Using mitochondrial and nuclear sequences, we generated a Bayesian population‐level phylogeny of the Thoropa miliaris species complex. We found deep genetic divergences among five geographically distinct clades. Southern clades were monophyletic and nested within paraphyletic northern clades. Analyses of historical demographic patterns suggest an overall north to south population expansion, likely associated with regional differences in habitat stability during the Pliocene and early Pleistocene. However, genetic structure among southern populations is less pronounced and likely represents more recent vicariant events resulting from Holocenic sea‐level oscillations. Our analyses corroborate that the Atlantic Coastal Forest has been a biogeographically dynamic landscape and suggest that the high diversity of its fauna and flora resulted from a combination of climatic and geologic events from the Pliocene to the present.

Sex and status in a cooperative breeding fish: behavior and androgens - Julie K. Desjardins; Kelly A. Stiver; John L. Fitzpatrick; Nicole Milligan; Glen J. Van Der Kraak; Sigal Balshine (Behavioral Ecology and Sociobiology, 2008)

A gene family of putative immune recognition molecules in the hydroid Hydractinia - Ryan S. Schwarz; Linda Hodes-Villamar; Kelly A. Fitzpatrick; Matthew G. Fain; Austin L. Hughes; Luis F. Cadavid (Immunogenetics, 2007)

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)